Effects of rail pressure control on fuel consumption, emissions and combustion parameters in a turbocharged diesel engine. Issue 1 (1st January 2020) - Zamboni, Giorgio; Capobianco, Massimo
Abstract: The influence of rail pressure control on fuel consumption, emissions and combustion in an automotive downsized turbocharged diesel engine was investigated, considering different operating modes in three-part load working conditions. These modes were selected according to the results of a previous step of the study, where low NOX and fuel consumption levels were obtained managing a hybrid exhaust gas recirculation (EGR) system and the turbocharger variable nozzle turbine (VNT). Aiming at limiting observed soot penalties, increased values of rail pressure were applied, deepening the interactions with engine-controlled sub-assemblies and the related variations in operating, environmental, energy and combustion parameters. At low levels of engine speed and load, major reduction in NOX emissions and fuel consumption were observed, with acceptable soot and noise combustion increase, while turbocharger speed was also enhanced. No variations in fuel consumption were achieved at higher load and speed, while soot penalty remained significant. A simplified method to describe and model engine behaviour and combustion process was also developed, defining linear relationships between rail pressure and engine quantities, including a wide set of combustion parameters derived from in-cylinder pressure diagrams and heat release curves.